Therapeutic Impact of GLP‐1 Receptor Agonists on Parkinson's Disease: A Scoping Review - João Pedro Henriques; João Pedro Stringhetta Rahal; Rafael da Cunha Gomes Ribeiro; Enzo Bogucheski Ribeiro Machado; Carlos Antonio Negrato (Neurology and Clinical Neuroscience, 2026)
ABSTRACT No disease‐modifying treatment exists for Parkinson's disease (PD). Glucagon‐like peptide‐1 receptor agonists (GLP‐1 RAs) have gained attention as promising candidates for neuroprotection, given documented expression of GLP‐1 receptors within the central nervous system and the contribution of brain insulin resistance to dopaminergic neurodegeneration. This scoping review sought to map the effects of GLP‐1 RA therapy on both motor and non‐motor outcomes among PD patients, irrespective of diabetes mellitus status. Guided by PRISMA‐ScR and the Joanna Briggs Institute methodology, a comprehensive search of PubMed/MEDLINE, LILACS, Embase, Scopus, and Web of Science was conducted to identify studies assessing the effects of GLP‐1 RA therapy in PD patients. Two reviewers independently carried out screening and data extraction. Seven studies were included: four independent randomized, double‐blind, placebo‐controlled trials, together with three secondary/post hoc analyses derived from a single additional Phase 2 exenatide trial cohort ( n = 62). Motor stabilization was observed in Phase 2 trials of lixisenatide and exenatide, whereas primary outcomes were neutral in both the Phase 3 EXENATIDE‐PD3 trial and the Phase 2 NLY01 trial. Post hoc analyses revealed improvements in mood, cognition, and emotional well‐being, together with evidence of brain insulin signaling activation detected through neuron‐derived exosomes. A tremor‐dominant phenotype, shorter disease duration, and younger age were each associated with a greater motor response. GLP‐1 RAs show a biologically plausible neuroprotective effect in PD, though the supporting evidence varies considerably across trial phases. Phase 3 trials that are phenotype‐enriched and biomarker‐guided are needed to clarify the conditions under which meaningful disease modification can be achieved.